Pengaruh Program Gerakan Literasi Sekolah terhadap Minat Baca Siswa Desa Pargadungan - Yuswitari Pasaribu Pasaribu; Rizky Akbar Situmeang; Helva Diansyah Putri; Novariany Novariany; Melsa Siagian; Zainuddin Zainuddin (LPPM Institut Nasional Laa Roiba Bogor, 2023)
It is known that in Indonesia there are as yet many individuals who are keen on perusing, in all circles and particularly understudies and understudies who are sorted as individuals who are battling in the realm of training. reading is because people do not understand how the benefits or functions of literacy are. difficulties when carrying out reading activities. Currently, the government has set a regulation to develop the literacy movement by routinely making a student read for approximately 10-15 minutes before carrying out the lesson. The core of this research is students or students from elementary school to high school. Then for the detailing of the issue, in particular: 1) How is the influence of the School Literacy Program to increase reading interest in students? 2) What are the difficulties or obstacles in literacy? And as for the purpose of this analysis to find the influence and constraints on the GLS program on students' reading interest in elementary school to high school. Qualitative is this analysis. Then the data collection stage used is a questionnaire. The results of this study indicate that students' or students' reading interest or interest increases, it can be observed from the results of the questionnaire which shows that a student's reading interest increases after the GLS is made, students' literacy programs usually increase, students' reading activities can be observed, and students' reading skills improve well by fostering a culture of literacy for students. Keywords: Impact, SchoolLiteracy Development, ReadingInterest